Processing of Experimental Data on the Results of Pedagogical Experiment by Means of Computer Statistical Packages - Chorna, Alyona (Pedagogical Discourse, 2013)
The article outlines the need for computer software for data processing as a result of teaching experiment. The basic criteria for selection of statistical methods of verification. It deals with existing computer statistical packages for data processing as a result of teaching experiment. The comparative characteristics of the products and an overview of the main features of the methods and criteria of mathematical statistics, graphing, diagramming, output reports. According to the hypothesis of pedagogical experiment, the depth of the research specialist can choose the appropriate statistical test and a computer package for the processing of the data for the selected criteria.